Agama dan budaya: Kesenian hadrah ishari di wilayah Pasuruan dan upaya pelestarian seni hadrah ishari - Ilmiyah, Bachrotul (Maliki Interdisciplinary Journal, 2024)
Religion formed from religion arises because of a process of interaction between the holy book which is believed by a believer of religion, but is conditioned in the context of the perpetrator’s life such as geographical factors, culture, and various objective conditions. Culture is the result of creativity, work, human initiative. Culture is born because of the habits that are carried out by a group or individual community. Religion and culture are elements that are interrelated or related, in society these two elements are always there and always have a relationship. Culture and religion influence each other, religion influences culture and vice versa, culture influences religion. Culture can change over time and with the times, many new arts have started to emerge. So that old arts are starting to be forgotten, so that these arts are not forgotten, efforts must be made. For example, efforts to preserve hadrah ishari art, which is in the Pasuruan area. Hadrah Ishari is a religious art in the form of a prayer for the Prophet Muhammad accompanied by the strains of a tambourine (flying) which has a unique rhythm or melody. This ishari art originates from Pasuruan, East Java and was founded by K.H Abdurrahim founded in 1918. The purpose of ishari itself is for Muslims, especially young children, to love and like sholawat more. So that the arts that have existed for a long time are not forgotten, we as young children who are Muslim need to preserve Hadrah Ishari. These conservation efforts can be done in various ways such as studying hadrah ishari art, participating in hadrah ishari art activities, introducing hadrah ishari art, and making hadrah ishari art an identity.